Atomic Processes in Basic and Applied Physics - Shevelko, Viacheslav; Tawara, Hiro.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The book is a comprehensive edition which considers the interactions of atoms, ions and molecules with charged particles, photons and laser fields and reflects the present understanding of atomic processes such as electron capture, target and projectile ionisation, photoabsorption and others occurring in most of laboratory and astrophysical plasma sources including many-photon and many-electron processes. The material consists of selected papers written by leading scientists in various fields.
From the content: Laboratory and astrophysical plasmas -- Modern view on ball lightning: Observations, experiments, theories -- Unravelling the mysteries of matter surrounding supermassive black holes -- Spectroscopic diagnostics of hot coronal plasma -- Hot spots and giant spiders clouding the solar sky -- Populations of excited parabolic states of hydrogen beam in fusion plasmas -- Atomic processes in dusty plasmas.-Atomic and Molecular Data Need for Industrial Application Plasmas -- Atomic collisions -- Charge transfer dynamics in low to intermediate energy ion-atom/molecule collisions studied by momentum imaging techniques -- Single and Multiple Electron Loss by Heavy Ions -- Target-density effects in atomic collisions -- Excitation and ionization in atom-atom collisions -- Atomic collisions in liquid targets -- Excited states of atomic hydrogen in reflected neutrals at high-Z metal surfaces -- The long-range interaction effects in collisions of Rydberg atoms with neutral targets -- Useful formula and Internet resources for ionic collisions -- Applications. Atomic Processes and Data Requirements in Tumor Therapy -- Atomic X-Ray Physics at the Experimental Storage Ring ESR -- Atomic physics using highly intense X-ray pulses -- Cascade of atomic displacements with account for ion-ion cross sections in solid state.
Keywords: Physics; Physics; Atomic, Molecular, Optical and Plasma Physics; Measurement Science and Instrumentation